Juvenile hormone modulates hydrocarbon expression and reproduction in the german wasp Vespula germanica - da Silva, Rafael Carvalho; do Nascimento, Fabio Santos; Wenseleers, Tom; Oi, Cintia Akemi (Frontiers in Ecology and Evolution, 2022)
Juvenile hormone (JH) affects multiple physiological traits in insects. In social insects, besides development, JH has been demonstrated to influence caste determination and the production of chemical compounds. In social wasps, JH triggers behavioral maturation, gonadotropic effects, and hydrocarbon modulation. Here, we investigated whether JH displays the same function in fertility and fertility cue production in females of the German wasp Vespula germanica, previously shown in the related species Vespula vulgaris. By experimentally treating workers with JH-analog, an anti-JH, and acetone solvent control, we tested whether JH modulates the cuticular chemical expression (CHCs), the Dufour’s gland chemical composition, and hence the compounds found over the egg’s surface. Additionally, we explored whether JH has a gonadotropic effect on workers. Workers treated with the JH-analog acquired a chemical profile that was intermediate between the queen and other treated workers. Interestingly, the same pattern was also seen in the Dufour’s glands and eggs, although more subtle. Furthermore, workers treated with the JH-analog were more fertile when compared to the controls, supporting the fact that JH acts as a gonadotropic hormone. Our results indicate a similar function of JH in societies of related wasp species V. germanica and V. vulgaris.